Correlational Study on Job Insecurity and Psychological Well being among Daily Workers - Christopher Robert Muljo; Umi Anugerah Izzati (Pusat Riset dan Inovasi Nasional, 2026)
The globalization era and Industrial Revolution 4.0 have driven the growth of daily workers systems across various industrial sectors, including agricultural manufacturing, creating job insecurity issues for workers. The target of this research is to examine the relationship between job insecurity and psychological well-being of daily workers in the agricultural industry. This research employed a quantitative method using the Pearson product-moment correlation analysis, with a sample of 118 daily workers selected through purposive sampling, and the questionnaire collection process used the job insecurity and psychological well-being scales that has been developed and tested. The results revealed that there is a significant negative relationship between job insecurity and psychological well-being among daily workers [r = - 0,629, p < 0.05], indicating that a high level of job insecurity can lead to lower levels of psychological well-being for daily workers. These findings reveal that employment uncertainty, lack of social security, and minimal legal protection experienced by daily workers negatively impact their psychological well-being, starting from self-acceptance, autonomy, environmental mastery, and other factors. This study concludes that job insecurity correlates with the psychological well-being aspect of daily workers, emphasizing the need for companies to provide job security and social guarantees to enhance workers' psychological condition and work productivity.